Perencanaan Sumber Daya Manusia Pendidikan - Diah Robiatul Adawiah; Puji Ambarwati; Pupu Marpuah; Faizal Djabidi; Eneng Muslihah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Human resource planning (HR) is a series of activities carried out to optimize the role of human resources to achieve organizational goals. This article aims to discuss Human Resource Planning in Educational Institutions. The research method used in literature studies is a descriptive approach. The results of the study show that there are four components in HR planning, including: job analysis, job description, job specification, and job design. Human resource planning in education cannot be separated from the competency standards of educators and education personnel in accordance with laws and regulations, namely, pedagogic, personality, professional and social competence. These competency standards are the basis for recruiting and selecting according to the needs of the institution as a school culture based on environmental conditions (internal and external). The importance of HR planning lies not only in the achievement of individual success but also in the contribution of educational institutions to the development of a better and more competitive society.